EVALUASI SELEKTIVITAS DAN KERAMAHAN LINGKUNGAN ALAT TANGKAP DOGOL DI KABUPATEN PANGANDARAN PROVINSI JAWA BARAT - Lantun Paradhita Dewanti; Izza Mahdiana; Irfan Zidni; Heti Herawati (Jurnal Airaha, 2018)
The purpose of this study was to determine the selectivity and level of environmental friendliness of mini bottom trawl in Pangandaran District. This research conducted on May-October 2017. Primary data obtained from purposive sampling either by interview or observation Selectivity indicator used was selectivity of catch species and size. Environmental friendly fishing was evaluated based on the FAO criteria. The result showed that catch rate of mini bottom trawl was 26.45 kg/hour. The main catch of mini bottom trawl in Pangandaran District was Trachypenaeus asper amount of 39,5% while by catch was Acetes sp¸ Oiolithes ruber, Trichiurus lepturus, and others catch with amount 60,40%. Catch size of mini bottom trawl main catch was ranged 4 cm - 9.90 cm. The main catch was 39,00% was more than size capture and under size capture was 61.00%. Catch utilization of this fishing gear was 93%. The result evaluation of environmental friendliness based on catch selectivity was 6 point which mean ‘less environmentally’ friendly while FAO criteria showed 18 point which mean ‘not environmentally’ friendly fishing.